The impact of corporate governance and the covid-19 crisis on earnings management practices in the tourism sector - Sebastian, Marcellino Ferdinand; Irawan, Ferry (Educoretax, 2025)
The objective of this quantitative research is to examine how the COVID-19 pandemic and elements of corporate governance influence earnings management in tourism-related businesses in Indonesia. The absolute value of discretionary accruals based on the Kothari model is used as the dependent variable to measure earnings management. Internal ownership, board size, the percentage of independent commissioners, audit committee participation, and a dummy variable for the COVID-19 pandemic constitute the independent variables of this study. Leverage (DER), profitability (ROE), and the market price-to-book value ratio (PBV) are also included as control variables in this research. With a total of 80 observations collected through purposive sampling, the research sample consists of 20 tourism sector companies listed on the Indonesia Stock Exchange for the period of 2020–2023. Panel data regression using STATA 17 software was used for data analysis. The research findings indicate that while board size, the percentage of independent commissioners, and the COVID-19 program do not significantly influence earnings management, internal ownership and audit committee activity do.